Effect of Eu3+ Doping on Electrical Transport Properties of LaMnO3. Issue 3 (March 2021) - Chen, Jinhuan; Xing, Ru; Zhao, Jianjun
Abstract: Perovskite manganese oxide La0.87 R0.13 MnO3 (R=La, Eu) polycrystalline samples were prepared by high temperature solid-phase reaction. The crystal structure was studied by X-ray diffraction (XRD). Through the resistivity-temperature ( ρ-T ) curve, the electrical transport properties are studied. The magnetoresistance-temperature ( MR-T ) curve was made to study the magnetoresistance effect. The results show that all samples in this group have good monophasic property and belong to orthorhombic system. In the measured temperature region, it belongs to semiconductor material, and the average ion radius of A position is different, and the influence of external magnetic field on electric conduction is different. The ρ-T curve fitting of the samples of this group shows that the samples of this group all follow the conduction mode of variable range jump in the measured temperature region. The magnetoresistance effect of Eu 3+ doped samples is significantly increased, which is beneficial to the practical application of magnetoresistance.